Spatial Variation of Population Density and Age Structure of White-Tailed Deer (Odocoileus virginianus) in a Colombian Moor - Carrillo-Villamizar, Jennifer Zilenthsjigh; López-Arévalo, Hugo Fernando (THERYA, 2024)
Wildlife population density is affected by resource availability, predators and competitors, and anthropogenic stressors. Its analysis and the factors affecting it are important for conservation, use, or population control. Based on estimates of density and population parameters, together with niche modeling, previous studies considered that the white-tailed deer population at the Chingaza National Natural Park (NNP) is undergoing exponential growth due to the marginal influence of factors regulating its abundance, such as predators. The aim of this study was to evaluate the population density and age structure of the white-tailed deer in the Chingaza NNP, Colombia. To evaluate the population density and age structure of white-tailed deer in the Monterredondo and La Paila sectors of the Chingaza NNP, 10 transects were installed with circular plots in each. These were visited twice; in each visit, we collected all deer pellet groups, measuring each pellet to estimate its volume. Population density was calculated using the Eberhardt and Van Etten method and the semi-automated PELLET procedure using FSC and FAR techniques; the age structure was estimated by k-means and fuzzy clustering analyses. With the FAR technique, the estimated deer density was 2.09 ind/km2 in Monterredondo and 0.94 ind/km2 in La Paila. With PELLET, these values were 0.37 ± 0.4 ind/km2 for Monterredondo and 0.16 ± 0.2 ind/km2 for La Paila. The proportion of age classes (adult, juvenile, and fawn) was 1:0.29:0 for Monterredondo and 1:0.57:0.04 for La Paila. The population density of white-tailed deer in two sectors of the Chingaza NNP is not homogeneous, but shows temporal and spatial variations. Population density has decreased versus reports from previous studies in this same area, with the highest deer abundance recorded in 2004, mostly in the Monterredondo sector. The proportion of age classes suggests that the population is stable, as the largest proportion of individuals corresponds to the adult stage